mTOR inhibition triggers mitochondrial fragmentation in cardiomyocytes through proteosome-dependent prohibitin degradation and OPA-1 cleavage - Hugo E. Verdejo; Valentina Parra; Andrea del Campo; Cesar Vasquez-Trincado; Damian Gatica; Camila Lopez-Crisosto; Jovan Kuzmicic; Leslye Venegas-Zamora; Ursula Zuñiga-Cuevas; Mayarling F. Troncoso; Rodrigo Troncoso; Beverly A. Rothermel; et al. (Cell Communication and Signaling)
Abstract Introduction Cardiac mitochondrial function is intricately regulated by various processes, ultimately impacting metabolic performance. Additionally, protein turnover is crucial for sustained metabolic homeostasis in cardiomyocytes. Objective Here, we studied the role of mTOR in OPA-1 cleavage and its consequent effects on mitochondrial dynamics and energetics in cardiomyocytes. Results Cultured rat cardiomyocytes treated with rapamycin for 6–24 h showed a significant reduction in phosphorylation of p70S6K, indicative of sustained inhibition of mTOR. Structural and functional analysis revealed increased mitochondrial fragmentation and impaired bioenergetics characterized by decreases in ROS production, oxygen consumption, and cellular ATP. Depletion of either the mitochondrial protease OMA1 or the mTOR regulator TSC2 by siRNA, coupled with an inducible, cardiomyocyte-specific knockout of mTOR in vivo, suggested that inhibition of mTOR promotes mitochondrial fragmentation through a mechanism involving OMA1 processing of OPA-1. Under homeostatic conditions, OMA1 activity is kept under check through an interaction with microdomains in the inner mitochondrial membrane that requires prohibitin proteins (PHB). Loss of these microdomains releases OMA1 to cleave its substrates. We found that rapamycin both increased ubiquitination of PHB1 and decreased its abundance, suggesting proteasomal degradation. Consistent with this, the proteasome inhibitor MG-132 maintained OPA-1 content in rapamycin-treated cardiomyocytes. Using pharmacological activation and inhibition of AMPK our data supports the hypothesis that this mTOR-PHB1-OMA-OPA-1 pathway impacts mitochondrial morphology under stress conditions, where it mediates dynamic changes in metabolic status. Conclusions These data suggest that mTOR inhibition disrupts mitochondrial integrity in cardiomyocytes by promoting the degradation of prohibitins and OPA-1, leading to mitochondrial fragmentation and metabolic dysfunction, particularly under conditions of metabolic stress.